Defy : [large type] the power of no in a world that demands yes - Sah, Sunita (Professor) (Random House Large Print, 2025)
This comprehensive exploration of defiance examines the pressures that silence us and offers research-based strategies to resist compliance, featuring real-world examples and practical tools to empower individuals to speak up and act in alignment with their values.